Audit Tata Kelola TI Berbasis COBIT 2019 di Politeknik XYZ - Nurul Ilma Hasana Kunio; Ema Utami; Alva Hendi Muhammad (Universitas Batanghari Jambi, 2022)
An IT governance audit is a way to evaluate the course of IT governance in an organization so that it can be seen whether the implementation of IT governance in the organization is in accordance with the guidelines and standards or not. The results of the audit will be reported to stakeholders so that they can be followed up. This research will use the COBIT 2019 framework in conducting IT audits. This study aims to determine the quality of service, management performance and determine the risks that occur at XYZ Polytechnic. From the results of the assessment on the capability level in the domains BAI03, BAI06, BAI07, and BAI10, it was found that these domains are the top four values in the COBIT design factor.